Measuring meaningful learning experience: confirmatory factor analysis - Ghazali, Norliza; Nordin, Mohamad Sahari (International Journal of Innovation, Creativity and Change., 2019)
A meaningful learning environment is important in the 21st century educational landscape. Meaningful learning engages students in dynamic instructional activities which can facilitate learning in the 21st century , and thus encourage the growth of holistic human characteristics. However, limited research has explored and measured the factors of meaningful learning. Thus, the purpose of this study is to identify the underlying factors that measure meaningful learning experience among university students in Malaysia. The study conceptualises meaningful learning experience in five dimensions (i.e. cooperative learning, active learning, authentic learning, constructive learning, and intentional learning). Data was collected with a 31-item questionnaire, the reliability of which indexes range from 0.838 to 0.885 in dimensions. The study population consists of University students who willingly volunteered to participate in the research (N=1,524). A sample of 603 respondents was drawn through simple random sampling. Confirmatory Factor Analysis (CFA) was used to analyse the data. The findings of the study indicates that the measurement model for meaningful learning achieved an acceptable level of fit. All statistics provide empirical evidence towards the fact that the meaningful learning measurement model is also psychometrically sound in terms of validity and reliability. The study concludes that there are five underlying factors measuring meaningful learning experiences, identified as cooperative learning, active learning, authentic learning, constructive learning and intentional learning. The study suggests that these factors are aspects of meaningful learning experiences that require development of the 21st century educational landscape which may lead to a more meaningful teaching and learning process.